On the accuracy of aposteriori error estimators - Čiegis, Raimondas; Suboč, Olga (Lietuvos matematikos rinkinys, 2000)
The analysis of the accuracy of the a posteriori error estimation procedure for finite-element solutions is presented. Simple error estimators of residual type are constructed, they allow error estimation in any norm with little extra effort. Results of numerical experiments are presented.